Islamic Education in Early Childhood: Cooperation between Parents and School To Build Character in Disruption Era - Burhan Nudin (Millah: Journal of Religious Studies, 2020)
To build Islamic education for children in their early age requires a good understanding of Islamic values itself and technically also demand good cooperation from parents in house for children character building, the presence of teacher in the school and the support of a conducive environment. And this what is called ‘Tripusat Pendidikan’, which recognize the existence of educational centers which affect the process of growth and development of a child to face an era that difficult to predict the changes and the danger for children, the era that known as era of disruption. This work explains how to inculcate early childhood Islamic education concepts, which is implemented in the form of collaboration between parents and schools in an effort to shape children's character in responding to the challenges of today's disruption era. The inculcation of religious values is an important matter which is expected to be able to minimize the negative impacts of the Disruption era. Through the inculcation of religious values in children, it is expected that in the future children will have good character, responsibility and always remember Allah, that whatever is done by children will have positive values and be useful for themselves and others.